Olive and the big secret - Freeman, Tor (Somerville, Mass. : Templar Books, 2012)
"Olive learns the hard way that keeping secrets is tough, and telling them can make for a whole lot of trouble!"--
Keywords: Secrets; Animals; Cats; Rumor; Friendship